Effects of microwave-vacuum drying on drying kinetics and quality of Orthosiphon aristatus (blume) Miq. Leaves and Eurycoma longifolia jack roots - Ismail @ Dahlan, Hada Masayu (2016)
Orthosiphon aristatus (OA) is known locally as misai kucing; belongs to the family Lamiaceae. Previous studies have shown that the leaves of OA have beneficial effects including anti-oxidant, anti-hypertensive and diuretic effect. Another herb, Eurycoma longifolia (EL) is well-known for its local name as tongkat ali; belongs to the family Simaroubaceae. Previous research has shown that the roots of EL have beneficial effects including anti-malarial, anti-bacterial and anti-pyretic. The presence of the properties that are beneficial in both herbs have shown that extracts from these materials have great potential in the development of various healthcare products. However, research in the area of processing for the production of bioactive compounds still insufficient. This research studied the effects of microwave-vacuum drying (MVD) techniques of OA leaves and EL roots and determined the optimum drying condition based on drying kinetics and phytochemicals content. Optimum condition of convection oven drying obtained at 45°C for the leaves and 60°C for the roots were selected and used as the control drying method in the study. The MVD experimental runs and optimization work were designed using Centralcomposite of Response Surface Methodology (RSM). Thirteen experiment points were obtained from RSM with microwave-power ranged from 150 – 300 W and vacuum pressure ranged from15 – 50 kPa. Experiments were carried out at continuous and intermittent modes. The effects of the two variables on phytochemicals of OA leaves and EL roots were investigated. Quality indicator selected for the leaves and the roots were Rosmarinic acid (RA) and Eurycomanone (EUR), respectively. At intermittent mode, three pulsation ratio (PR) of 2, 3 and 4 were studied. Three thinlayer drying models namely Page, Midili and Logarithmic were applied to fit the experimental data in order to select the best model to represent MVD process for both type of herbs. The optimum MVD conditions at continuous mode for the highest RA content of OA leaves were obtained at 300 W microwave power and 50 kPa vacuum pressure. The optimum responses of the process were: RA 556.28 mg/L and drying time 17.14 minutes. Whereas for optimum MVD conditions at intermittent mode, PR 3 was found to be the most suitable condition with 700.39 mg/L of RA concentration in the dried leaves. On the other hand, for EL roots, the optimum MVD conditions at continuous mode for the highest EUR content were obtained at 150 W microwave power and 50 kPa vacuum pressure. The optimum responses of the process were: EUR 7.92 mg/L and drying time 18.64 minutes. Whereas for optimum MVD conditions at intermittent mode, PR 4 was found to be the most suitable condition with 3.58 mg/L of EUR concentration in the dried roots. Midili model was found to be the most suitable model to describe the MVD process of both types of herbs with root mean square error (RMSE) ranged from 0.9953 – 0.999 for OA leaves and 0.9666 – 0.999 for EL roots. MVD at 300 W microwave power and 50 kPa vacuum pressure, at intermittent mode, with PR 3 was found out to be the most suitable drying method for the microwavevacuum drying technique for OA leaves as it contained the highest amount of RA. While, for EL roots, MVD at 150 W microwave power and 50 kPa vacuum pressure, at continuous mode was found out to be the most suitable drying method for the microwave-vacuum drying technique for EL roots however it contained less amount of EUR as compared to EUR from control drying method.